Cleft deformities in adults and children aged over six years in Nigeria: Reasons for late presentation and management challenges - Wasiu L Adeyemo; Mobolanle O Ogunlewe; Ibironke Desalu; et al (Dove Medical Press, 2009)
Wasiu L Adeyemo1, Mobolanle O Ogunlewe1, Ibironke Desalu2, Akinola L Ladeinde1, Bolaji O Mofikoya3, Michael O Adeyemi4, Adegbenga A Adepoju4, Olufemi O Hassan41Department of Oral and Maxillofacial Surgery, Faculty of Dental Sciences, 2Department of Anaesthesia, 3Department of Surgery, Faculty of Clinical Sciences, College of Medicine, University of Lagos, Lagos, Nigeria; 4Department of Oral and Maxillofacial Surgery, Lagos University Teaching Hospital, Lagos, NigeriaAbstract: In developing countries, untreated cleft lips and palates are found with increasing frequency and patients often present to the surgeon far past the optimal time for closure of the cleft deformities. A prospective study was conducted between March 2007 and September 2009, to identify the reasons and treatment challenges of delayed presentation of cleft lip and palate deformities at the Lagos University Teaching Hospital, Nigeria. Out of a total of 150 patients with cleft defects during the period, 43 (28.7%) were adults and children aged over six years. The mean age of these patients at the time of presentation was 17.3 years. The most common reasons for late presentation were lack of money (56.7%), lack of health care services nearby (18.4%), and lack of awareness of treatment availability (13.3%). Common challenges in these patients included surgical, orthodontic, speech, anesthetic, and psychological. Although adult clefts were significantly enlarged in three dimensions the anatomic landmarks were easier to discern than in an infant. However, extensive soft tissue dissection in adult cleft lip repair resulted in significant postoperative edema. Closure of wide palatal cleft often required the use of adjunct intraoral flaps. Despite late presentation, surgical outcome of these patients was satisfactory and comparable to cleft repair in infants.Keywords: cleft deformities, adults, adolescents, late presentation, management, challenges